Prognostic Value of Metabolic and Volumetric Parameters of Preoperative FDG-PET/CT in Patients With Resectable Pancreatic Cancer - Im, Hyung-Jun (Wolters Kluwer Health, 2016)
In this study, we aimed to evaluate prognostic value of metabolic and volumetric parameters measured from 18F fluorodeoxyglucose-positron emission tomography/computed tomography (FDG-PET/CT) in patients with resectable pancreatic cancer.